Estudo com webquests brasileiras e portuguesas disponíveis na web : uma análise exploratória sobre a quantidade, qualidade, conteúdo e a usabilidade - Bottentuit Junior, João Batista (2008)
A WebQuest is a very simple model and rich to use the educational potential of the Web, on the grounds of collaborative learning and research in the processes for the construction of knowledge, which currently has thousands of proposals for educators from various parts of the world. However, many of WebQuests available online does not meet the minimum standards of quality in terms of components and usability, or they are not more than sheets of simple exercises or "WebExercises." This article was reported and analyzed 483 WebQuests English that were made available online between July and October 2007. The evaluation focused on the components and on some indicators associated with usability. The results show that, with respect to the components, the biggest failures are in the task, the resources and evaluation, and the level of usability, the largest failure to report is the absence of the "menu" in many of the specimens examined. It was also found that only 41% were real WebQuests, with other simple "WebExercises" with routine activities that do not take the student to harness the potential of the Web for the construction of knowledge.